Admission to hospital with asthma. Issue 7 (July 1985) - Conway, S P; Littlewood, J M
Abstract : The circumstances surrounding 142 hospital admissions for acute asthma in 110 children during a one year period were examined. Thirty four of 106 (32%) children with previous wheezing had not been diagnosed as asthmatic, nor received effective antiasthmatic medication. Nineteen of 36 (53%) known, but undertreated, asthmatics were under the care of the hospital paediatricians. Twenty-four of 58 (41%) regular school attenders had missed more than 11 days' school in the previous year. Good parental understanding of their child's illness was strongly associated with adequate treatment. Parental understanding was, however, poor in 58 of 137 (42%) admissions. Control of inadequately treated chronic symptoms was obtained by simple and straightforward changes in treatment.